2008
DOI: 10.1080/14756360802201223
|View full text |Cite
|
Sign up to set email alerts
|

Particular interaction between pyrimethamine derivatives and quadruple mutant type dihydrofolate reductase of Plasmodium falciparum: CoMFA and quantum chemical calculations studies

Abstract: Comparative molecular field analysis (CoMFA) was performed on twenty-three pyrimethamine (pyr) derivatives active against quadruple mutant type (Asn51Ile, Cys59Arg, Ser108Asn, Ile164Leu) dihydrofolate reductase of Plasmodium falcipaarum (Pf DHFR). The represented CoMFA models were evaluated based on the various three different probe atoms, C sp3 (þ1), O sp3 (21) and H (þ1), resulting in the best model with combined three types of probe atoms. The statistical results were r 2 cv ¼ 0.702, S press ¼ 0.608, r 2 nv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Of particular note is the fact that the basic structural information proves that the cause of the Cyc resistances in the quadruple mutant type PfDHFR came from the steric clash of the Asn108 mutation with the repulsive interaction energies, as shown in Fig. 6b, similar to that found with Pyr [19]. On the other hand, the potent WR99210 inhibitor can avoid the steric clash with Asn108, so it does not generate any positive energy value.…”
Section: Different Interaction Energies Between the Cyc And Wr99210 Imentioning
confidence: 84%
See 1 more Smart Citation
“…Of particular note is the fact that the basic structural information proves that the cause of the Cyc resistances in the quadruple mutant type PfDHFR came from the steric clash of the Asn108 mutation with the repulsive interaction energies, as shown in Fig. 6b, similar to that found with Pyr [19]. On the other hand, the potent WR99210 inhibitor can avoid the steric clash with Asn108, so it does not generate any positive energy value.…”
Section: Different Interaction Energies Between the Cyc And Wr99210 Imentioning
confidence: 84%
“…This research has led to further work to establish a three-dimensional quantitative structure-activity relationship (3D-QSAR) and to its use to develop new and effective antifolate antimalarials against PfDHFRs. Very recently, we successfully investigated the 3D-QSAR of the Pyr derivatives using comparative molecular field analysis (CoMFA) technique to guide the design of new inhibitors of quadruple mutant (Asn51Ile, Cys59Arg, Ser108Asn, and Ile164Leu) PfDHFR [19]. Consequently, the CoMFA technique has been chosen to find the relationship between the Cyc derivatives structures and their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Maitarad et al carried out 3D-QSAR/CoMFA and 3D-QSAR/CoMSIA studies using cycloguanil analogs against wild type and quadruple mutant PfDHFR enzymes [47]. Recently, they also reported the result CoMFA and CoMSIA studies based on pyrimethamine derivatives active against quadruple mutant type PfDHFR enzyme [48]. To the best of our knowledge, no 3D-QSAR studies have been carried out based on the reported activities of cycloguanil derivatives against A16V + S108T mutant PfDHFR enzyme.…”
Section: Introductionmentioning
confidence: 94%
“…Two compounds from this class of series were found to be active with the IC 50 values of 100 μM and 400 nM against wild-type PfDHFR (Adane et al, 2014). Quantitative structure-activity relationship (QSAR) studies have also been extensively carried out on these known antifolates and their derivatives to identify structural features responsible for the differences in anti-plasmodial activities with respect to their electrostatic, steric, and hydrophobic nature (Adane & Bharatam, 2009;Basak & Mills, 2010;Basak, Mills, & Hawkins, 2011;Hecht, Cheung, & Fogel, 2008;Maitarad, Kamchonwongpaisan, et al, 2009;Maitarad, Saparpakorn, et al, 2009;Ojha & Roy, 2011;Santos-Filho, Mishra, & Hopfinger, 2001;Sivaprakasam, Tosso, & Doerksen, 2009). The studies reported slightly different binding alignment of the ligands to the mutant form of an enzyme as compared to the wild-type form.…”
Section: Introductionmentioning
confidence: 99%